Correction: Tajima et al. Amino Acids at Positions 156 and 332 in the E Protein of the West Nile Virus Subtype Kunjin Virus Classical Strain OR393 Are Involved in Plaque Size, Growth, and Pathogenicity in Mice. Viruses 2024, 16, 1237 - Shigeru Tajima; Hideki Ebihara; Chang-Kweng Lim (Viruses)
Missing Table [...]